Promoting sleep and rest of infants using nonpharmacological interventions within the neonatal intensive care unit at Children's of Mississippi. Issue 1 (14th March 2023) - Robinette, Bethany; Palokas, Michelle
ABSTRACT: Objective: This project aimed to promote evidence-based practices regarding the promotion of sleep and rest using nonpharmacological interventions for infants in the neonatal intensive care unit (NICU) at Children's of Mississippi. Introduction: Sleep is a basic physiological need that plays a fundamental role in the growth and development of infants. Unfortunately, infants admitted to the NICU after birth may not receive adequate sleep and rest, especially when compared to infants discharged home after delivery. Methods: The project used the JBI Practical Application of Clinical Evidence System (PACES) and Getting Research in Practice (GRiP) audit tool for promoting change in healthcare practice. A baseline audit of NICU staff and patient caregivers was conducted and measured against five best practice recommendations, followed by implementation of targeted strategies and a follow-up audit. Results: The project team discovered two barriers to sleep promotion and rest in the NICU at Children's of Mississippi: lack of nurse knowledge of evidence-based practices for promotion of sleep and rest for infants in the NICU and a lack of location in the electronic health record to document sleep quality of infants. Strategies were implemented to address these barriers and compliance improved in four of the five audit criteria. Conclusions: Implementation of an educational PowerPoint that focused on sleep promotion of infants in the NICU was developed and distributed to all of the nurses and resulted in average increased compliance from 43% to 53% for all audit criteria.